Academic Procrastination of Pre-Service Student-Teachers of Professional Education Program - Nova, Dahlia; Kadafi, Asroful; Dewi, Noviyanti; Da Costa, Augusto (IJORER : International Journal of Recent Educational Research, 2025)
Objective: Low human resource levels, particularly with relation to teacher quality, are one of the issues facing Indonesian education. In order to provide aspiring teachers with the knowledge and abilities necessary to become professional teachers, the Indonesian government has recently established a policy through a professional teacher education program. Professional teacher education students must submit assignments as part of their coursework, and they must transmit their completed assignments to the Learning Management System by the deadline. Students experience academic procrastination, or the inability to finish tasks on time, due to the workload of their integrated practical learning at school. The purpose of this study is to look at professional teacher education students' academic procrastination. Method: This study employs a quantitative methodology that includes the examination of descriptive data and the survey technique. Purposive sampling was the approach employed, and the sample consisted of ninety-seven pupils. The academic procrastination scale was utilized to collect data. Results:The analysis's findings demonstrate that students' levels of academic procrastination are quite high. Most participants scored highly on the feature of the desire to avoid labor and uncomfortable situations because they found it difficult to accomplish anything unpleasant. Novelty: Academic procrastination has been widely studied, but many problems of academic procrastination are still found in students. This study provides an overview that students in the teacher professional education program are still procrastinating so that, in the future, appropriate interventions can be given.